ANALISIS KURIKULUM TERHADAP DAYA MATEMATIK - Margana, Akhmad (Institut Pendidikan Indonesia, 2012)
Abstract Thinking is one human trait . Since can perceive , people begin to think and this process continues until the end of his life . Attitude and way of thinking can be developed through a process of learning mathematics because mathematics has a structure and a strong and clear linkages antarkonsepnya so anyone who thinks rationally skilled study . Therefore learning how mathematics can be implemented so as to cultivate students' mathematical power . Mathematics curriculum should be designed not only for students continuing on to higher education but also for entering the job market . Focus of the curriculum can be examined from three aspects , namely Intended Curriculum , Curriculum Implemented and Attained Curriculum . Learning process must be conducted in accordance with the class learning objectives to be achieved . Also, it can also refer to the implementation of the curriculum in other countries.